2008
DOI: 10.1080/10826080701884911
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Motivations for Recreational Marijuana Use Among Adult Canadians

Abstract: The Canadian Special Senate Committee on Illegal Drugs (2003) noted that little ethnographic research had been devoted to exploring why people use marijuana recreationally or the social contexts in which it is used. The purpose of this exploratory qualitative research is to better understand both of these neglected topics through interviews conducted with 41 adult Canadian users between 2005 and 2006. The participants' ages ranged from 21 to 61 and included 25 males and 16 females whose consumption patterns ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
58
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 51 publications
10
58
1
1
Order By: Relevance
“…This could be related to reduced emotional regulation in cannabis users, as suggested in a study by Dorard et al [59] , who reported higher anhedonia and alexithymia scores in cannabis users than in healthy controls. The most frequent reasons for cannabis use are related to enhancement of affective states [60,61] , including relaxation, an increase in pleasure and being high, thus supporting the hypothesis of impaired emotional regulation in cannabis users. Because the group differences were specific for one particular condition of the task, and because there were no group differences in baseline mood ratings, these findings cannot be explained by a generally lower mood in cannabis users.…”
Section: Discussionmentioning
confidence: 73%
“…This could be related to reduced emotional regulation in cannabis users, as suggested in a study by Dorard et al [59] , who reported higher anhedonia and alexithymia scores in cannabis users than in healthy controls. The most frequent reasons for cannabis use are related to enhancement of affective states [60,61] , including relaxation, an increase in pleasure and being high, thus supporting the hypothesis of impaired emotional regulation in cannabis users. Because the group differences were specific for one particular condition of the task, and because there were no group differences in baseline mood ratings, these findings cannot be explained by a generally lower mood in cannabis users.…”
Section: Discussionmentioning
confidence: 73%
“…Our goal was to elaborate some of the factors that may be driving the normalisation of cannabis in Canada. We were also interested in the kinds of social and cultural factors that might explain the emergence of more tolerant attitudes regarding the risks associated with cannabis that have been described in recent studies (Osborne andFogel 2008, Fischer et al 2011 This perspective was endorsed by participants across the four study sites. Most seemed to be of the view that the decision to use (or not to use) cannabis was a 'personal choice', as Susan put it, that was largely free of any lingering moral stigma or social disapprobation.…”
Section: Resultsmentioning
confidence: 98%
“…Meanwhile, the growth of 'medical marijuana' throughout North America, and its gradual legal support, bolsters this reassessment while doing much to advertise the putative benefits of cannabis use. Taken together then, as our participants attested, the growing prevalence of cannabis use across wide sections of Canadian society coupled with the low incidence of harm associated with this consumption and the growth of medical marijuana have converged to drive cannabis normalisation across the country (see also Osborne andFogel 2008, Duff et al 2012).…”
Section: Health Risk and Society 221mentioning
confidence: 88%
See 2 more Smart Citations